Tensional Responsiveness: Ecosomatic Aliveness and Sensitivity with Human and More-than - Weig, Doerte (transcript, 2021)
How we sense and move our bodies shapes how we relate with each other. Current socio-economic practices are reducing generative qualities of relating. Doerte Weig shows how bodily capacities for sensitive tensional responsiveness are relevant to (re)generative cultures, the future of work, lifelong learning, sharing, healing and well-being. She draws together her own experience of living with Baka egalitarian foragers in North-Eastern Gabon, her corporate experience, and her studies on bodying, somatics and our connective tissue-system fascia. Interweaving neurophysiological shifting-sliding with a radically different ecosystemic awareness opens up potentials for bodying beyond current legal and political limits into enchantingly vibrant and ecosomatically alive futures.